Clinical Study of DLBS2411, a Mucoprotector and Proton Pump Inhibitor Bioactive Fraction Derived From Cinnamomum burmanii, on the Intragastric Acidity - Raymond Rubianto Tjandrawinata; Murdani Abdullah; Marcellus Simadibrata; Liana W Susanto; Kaka Renaldi (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: DLBS2411, A bioactive fraction derived from the bark of Cinnamomum burmanii has been developed to address acid-related gastrointestinal disorders. This study evaluated the pharmacodynamic effect of DLBS2411 on the 24-hour intragastric acidity in healthy adults.